The Muslim Women and Challenges of the Contemporary Time - Opeloye, Muhib O. (2014)
Gender Studies is increasingly becoming an important field of academic study in view of the interest it has been generating, not only among the political scientists and philosophers but also the theologians. The interest generated in this field must have resulted from degradation to which womanhood has been subjected through the ages. It is a fact well known that the ancient civilizations such as the Byzantine's and Persian's as well as the primordial religions like Hinduism and Buddhism have nothing favourable about women who were held in very low esteem. It was Islam at its advent which accorded women due honour and dignity. Unfortunately, however, it was not long when due to some socio-cultural factors Muslim women were deprived of rights accorded them by Islam. The Muslim reformists of the 19th century including Muhammad Abduh and Jamalud Din al-Afghani tried with little success in the Muslim world to restore dignity and honour to womanhood.